Potential of Fables as Learning Resources for Environmental Education and Its Relevance to the Merdeka Belajar Curriculum - Holy Ichda Wahyuni; Agus Budiman; Ratno Abidin; Elmi Tri Yuliandari (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
The development of noble character, especially the awareness of protecting the environment, can be optimized through the internalization process in learning. Children's literary media is an effective medium, especially applied to elementary school-aged children at the golden age of character planting. Stories in children's literature can dialogue life in an interesting, concrete, and contextual way. The fable entitled